Coastal amplification of supply and transport (CAST): a new hypothesis about the persistence of Calanus finmarchicus in the Gulf of Maine. (18th January 2017) - Ji, Rubao; Feng, Zhixuan; Jones, Benjamin T.; Thompson, Cameron; Chen, Changsheng; Record, Nicholas R.; Runge, Jeffrey A.
Abstract: The lipid-rich calanoid copepod, Calanus finmarchicus, plays a critical role in the pelagic food web of the western North Atlantic and particularly in the Gulf of Maine ecosystem. Deep basins along the continental shelf harbour high abundance of diapausing C. finmarchicus during the summer and fall. In Wilkinson Basin in the western Gulf of Maine, C. finmarchicus has persisted in large concentrations despite recent significant warming that could potentially threaten the existence of the population in this region. Identifying the major source of diapausing individuals is critical to the understanding of mechanisms that allow population persistence. In this study, Lagrangian tracking experiments using an individual-based copepod life cycle model and simulation of environmental conditions during an exceptionally warm year (2012) suggest that coastal waters are the major upstream source for individuals entering dormancy in Wilkinson Basin over summertime, although pathways and distribution patterns vary with the release timing of particles. Both model results and observation data support the Coastal Amplification of Supply and Transport (CAST) hypothesis as an explanation for the persistence of C. finmarchicus population in the western Gulf of Maine. The mechanism involves the coastal amplification of supply (spring reproduction/summer growth in the food-rich coastal region) and transport to the receiving Wilkinson Basin that is capable of harbouring the diapausing stock.